SMART GARDEN SEBAGAI IMPLEMENTASI SISTEM KONTROL DAN MONITORING TANAMAN BERBASIS TEKNOLOGI CERDAS - Darmawan, I.W.B.; Kumara, I.N.S.; Khrisne, D.C. (Jurnal SPEKTRUM; Vol 8 No 4 (2021): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2021.v08.i04.p19, 2022)
Smart garden is a control system application to monitor watering/plant care that utilizes intelligent technology. This study reviews the components used in smart gardens and the application of smart gardens in community life. The components commonly used in smart garden such as BLYNK App, Antares, wireless sensor and actuators networks, SMS Gateway, capacitive soil moisture sensor, temperature sensor, light sensor, Arduino nano, Arduino uno R3, Arduino mega 2560, and Raspberry Pi. Smart garden has been applied in agriculture and farm with the aim of monitoring plant growth, optimizing harvest activities, developing ecotourism and Adiwiyata program.